2018
DOI: 10.1037/abn0000329
|View full text |Cite
|
Sign up to set email alerts
|

Atypical neural responding to hearing one’s own name in adults with ASD.

Abstract: Diminished responding to hearing the own name is one of the earliest and strongest predictors of autism spectrum disorder (ASD). Here, we studied for the first time the neural correlates of hearing one's own name in ASD. Based on existing research, we hypothesized enhancement of late parietal positive activity specifically for the own name in neurotypicals, and this effect to be reduced in adults with ASD. Source localization analyses were conducted to estimate group differences in brain regions underlying thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 78 publications
7
34
1
Order By: Relevance
“…These neural responses persist throughout the lifespan [Carmody & Lewis, 2006; Key, Jones, & Peters, 2016; Tamura, Mizuba, & Iramina, 2016], albeit with slightly shifting morphologies in neural response that stabilize considerably by adolescence [Eggermont & Moore, 2012; Mahajan & Mcarthur, 2015]. Prior electroencephalography (EEG) research has identified early neural responses to OON between 100 and 300 milliseconds (ms) over frontal scalp regions and late responses between 300 and 800 ms over frontal and posterior scalp regions, particularly when OON occurs only occasionally and unpredictably [Berlad & Pratt, 1995; Holeckova, Fischer, Giard, Delpuech, & Morlet, 2006; Nijhof, Dhar, Goris, Brass, & Wiersema, 2018; Pratt, Berlad, & Lavie, 1999]. These robust neural responses to OON can be elicited in both attentive and inattentive states, including even when participants are asleep or comatose [Fischer, Dailler, & Morlet, 2008; Perrin et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These neural responses persist throughout the lifespan [Carmody & Lewis, 2006; Key, Jones, & Peters, 2016; Tamura, Mizuba, & Iramina, 2016], albeit with slightly shifting morphologies in neural response that stabilize considerably by adolescence [Eggermont & Moore, 2012; Mahajan & Mcarthur, 2015]. Prior electroencephalography (EEG) research has identified early neural responses to OON between 100 and 300 milliseconds (ms) over frontal scalp regions and late responses between 300 and 800 ms over frontal and posterior scalp regions, particularly when OON occurs only occasionally and unpredictably [Berlad & Pratt, 1995; Holeckova, Fischer, Giard, Delpuech, & Morlet, 2006; Nijhof, Dhar, Goris, Brass, & Wiersema, 2018; Pratt, Berlad, & Lavie, 1999]. These robust neural responses to OON can be elicited in both attentive and inattentive states, including even when participants are asleep or comatose [Fischer, Dailler, & Morlet, 2008; Perrin et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Past research has demonstrated that neural measures of OON response in quiet settings are sensitive enough to differentiate individuals with ASD from TD controls. For instance, ASD‐V adults produce MMRs to OON that are similar in amplitude to that of TDs but LPPs/FNs to OON that are smaller in amplitude compared with that of TDs [Nijhof et al, 2018]. ASD‐V children, adolescents, and young adults show similarly reduced amplitude of LPPs when viewing their face or written name amidst other random names and faces [Cygan, Tacikowski, Ostaszewski, Chojnicka, & Nowicka, 2014; Gunji, Inagaki, Inoue, Takeshima, & Kaga, 2009; Nowicka, Cygan, Tacikowski, & Ostaszewski, 2016].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent electro-encephalography (EEG) studies found that the typical event-related potential (ERP; electrical changes in brain activity observed in response to a specific event) amplitude differences between seeing one's own face and another person's face was diminished in both autistic children and adults (Cygan, Tacikowski, Ostaszewski, Chojnicka, & Nowicka, 2014;Gunji, Inagaki, Inoue, Takeshima, & Kaga, 2009). Similarly, it has been shown that the ERP response to seeing (Cygan et al, 2014) or hearing (Nijhof, Goris, Brass, Dhar, & Wiersema, 2018) one's own name in autistic adults is diminished as well. In short, both physical (face) and first-order psychological (name) aspects of self-processing were shown to be atypical in autistic individuals in these studies, using paradigms that did not require second-order representation.…”
mentioning
confidence: 99%
“…Finally, EEG studies suggest that aspects of self-referential processing that appear typical at the behavioural level may be supported by different underlying neural mechanisms in individuals with autism (Cygan et al, 2014;Nijhof et al, 2018). Throughout development, autistic individuals may learn to compensate for their atypical neural functioning by relying on neural pathways that are different from their neurotypical peers.…”
mentioning
confidence: 99%